Uncovering the Driving Factors of Microtransactions: Digital Consumer Behavior, In-Game Events, and the Influence of FOMO among Generation Z In Indonesia - Brillyan Arthur; , Agus Putu Abiyasa (Amkop Management Accounting Review (AMAR), 2025)
The mobile gaming industry has grown rapidly in recent years, with an increasing number of players and significant revenues. One of the main sources of revenue for game developers is microtransactions, which are in-game purchases that allow players to obtain virtual goods or in-game currency. Although microtransactions have become an important source of revenue, there is still little research specifically examining the factors that influence digital consumer behavior in making microtransactions. This study aims to uncover the factors that drive microtransactions among the younger generation in Indonesia, focusing on digital consumer behavior, in-game events, and the influence of fear of missing out (FoMO). This study uses an online survey method with a sample of 250 respondents selected using purposive sampling techniques. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4.0 software. The results showed that digital consumer behavior, in-game events, and FoMO had a positive and significant effect on microtransactions. In addition, FoMO also acted as a mediator in the relationship between digital consumer behavior and in-game events on microtransactions. This study contributes to the understanding of digital consumer behavior and the factors that influence microtransactions among Generation Z in Indonesia.